In vitro antimicrobial activity of different gutta-percha points and calcium hydroxide pastes - Tanomaru, Juliane Maria Guerreiro [UNESP]; Pappen, Fernanda Geraldes; Filho, Mário Tanomaru; Palomari Spolidorio, Denise Madalena; Ito, Izabel Yoko (FapUNIFESP (SciELO), 2007)
The aim of this study was to evaluate the antimicrobial activity of different trademarks and compositions of gutta-percha points and calcium hydroxide pastes used in endodontic therapy. The evaluated material consisted of gutta-percha points containing calcium hydroxide (Roeko™), gutta-percha points containing chlorhexidine (Roeko™), two convencional gutta-percha points (Endo Points™ and Roeko™) and two calcium hydroxide pastes (Calen™ and Calen/PMCC™). Antimicrobial tests included five species of microorganisms: Escherichia coli (ATCC10538), Staphylococcus epidermidis (ATCC12228), Staphylococcus aureus (ATCC6538), Pseudomonas aeruginosa (ATCC27853), and Micrococcus luteus (ATCC9341). The Agar difusion method was employed. The plates were kept at room temperature for 2 h for prediffusion and then incubated at 37°C for 24 h. The triphenyltetrazolium chloride gel was added for optimization and the zones of inhibition were measured. Statistical evaluation was carried out using analysis of variance and Tukey Test. The obtained results showed that all microbial species used in the study were inhibited by the gutta-percha points containing chlorhexidine and by the calcium hydroxide pastes (Calen™ and Calen/ PMCC™), with similar results (p > 0.05). No antimicrobial activity was observed for the other groups. It was concluded that the gutta-percha points containing chlorhexidine presented antimicrobial activity, whereas the gutta-percha points containing calcium hydroxide did not.
Keywords: Calcium hydroxide; Chlorhexidine; Gutta-percha; Microbiology; calcium hydroxide; chlorhexidine; gutta percha; topical antiinfective agent; analysis of variance; drug effect; endodontics; Escherichia coli; Gram positive bacterium; microbiology; Micrococcus luteus; Pseudomonas aeruginosa; standard; Staphylococcus aureus; Staphylococcus epidermidis; tooth root; Analysis of Variance; Anti-Infective Agents, Local; Calcium Hydroxide; Endodontics; Gram-Positive Bacteria; Gutta-Percha; Tooth Root